Strategi Pembelajaran yang Efektif dalam Meningkatkan Kualitas Proses Belajar di TK Islam Al Azhar 43 Gorontalo - Arthika Rahmawati Ilam; Lestari B. Samaun; Meiranti Saputri S. Djawalu; Sucitra Muharam (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2024)
This study aims to identify and analyze effective learning strategies in improving the quality of the early childhood learning process at Al Azhar 43 Gorontalo Islamic Kindergarten. The research method used is descriptive qualitative with observation techniques to explore learning practices implemented by teachers in the classroom. The results show that the learning strategies applied are based on Islamic values and integrated thematic approaches, such as worship habituation, role play, Islamic storytelling, and Project-Based Learning. These strategies not only increase children's learning motivation, but also build character, social skills, and understanding of moral and religious values. However, there are limitations in the variety of learning models and the sustainability of the projects implemented. This study recommends the development of alternative strategies such as Beyond Centers and Circle Time (BCCT) and active story repetition to improve the stimulation of children's overall development. The findings are expected to serve as a reference in designing more effective and meaningful ECD learning.